2018
DOI: 10.1039/c7ee03013d
|View full text |Cite
|
Sign up to set email alerts
|

In situ simultaneous photovoltaic and structural evolution of perovskite solar cells during film formation

Abstract: Simultaneous GI-WAXS diffraction patterns and JV measurement of IBC solar cells during in situ anneal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
91
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 51 publications
1
91
0
Order By: Relevance
“…In this regard, in situ techniques play a critical role in providing time‐resolved information on the evolution of halide perovskites under various synthetic conditions. Recent reported in situ studies making use of diffraction measurements, terahertz spectroscopy, Fourier transform infrared spectroscopy, UV–vis spectroscopy, simultaneous X‐ray scattering and device performance, transmission electron microscopy, and spectrally ambiguous photoluminescence (PL) correlated with ex situ device performance gradually shed light on halide perovskite formation and its evolving material properties as well as on device performance. Despite these advancements, critical insights into phase formation and evolution of film properties occurring during spin‐coating and immediately after deposition go unobserved during the ≈2–5 min wet film transfer time prior to commencing subsequent in situ studies.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, in situ techniques play a critical role in providing time‐resolved information on the evolution of halide perovskites under various synthetic conditions. Recent reported in situ studies making use of diffraction measurements, terahertz spectroscopy, Fourier transform infrared spectroscopy, UV–vis spectroscopy, simultaneous X‐ray scattering and device performance, transmission electron microscopy, and spectrally ambiguous photoluminescence (PL) correlated with ex situ device performance gradually shed light on halide perovskite formation and its evolving material properties as well as on device performance. Despite these advancements, critical insights into phase formation and evolution of film properties occurring during spin‐coating and immediately after deposition go unobserved during the ≈2–5 min wet film transfer time prior to commencing subsequent in situ studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise solution‐to‐solid conversion of these advanced formulations is yet to be revealed, and their improved processability in the context of anti‐solvent dripping is yet to be quantified, let alone understood. Such knowledge potentially holds important clues to further progress in formulation engineering . To accurately describe the intermediate phases during spin‐coating, we adopt the Ramsdell notation, employed by Gratia et al For example, the well‐known yellow δ phase, called here the 2H phase, is a nonperovskite phase composed of pure hexagonal closed‐packed AX 3 layers, resulting in a 1D array of BX 6 face‐sharing octahedra.…”
mentioning
confidence: 99%
“…16,17 Several studies have confirmed the presence of transient crystalline precursor species. [18][19][20][21][22][23] The structure of mixed halide precursors has not been clearly determined and their formation kinetics depend on the lead counterion in the precursor. 20,21,24,25 Furthermore, previous studies have established that the film formation is a kinetically trapped process, indicating that the reaction coordinates depend on the film processing route (e.g., drop casting, spin coating, blade coating).…”
Section: Context and Scalementioning
confidence: 99%